Lactiplantibacillus pentosus P2020 protects the hyperuricemia and renal inflammation in mice - Wang, Zhihuan; Song, Liqiong; Li, Xianping; Xiao, Yuchun; Huang, Yuanming; Zhang, Yue; Li, Jintong; Li, Mingding; Ren, Zhihong (Frontiers in Nutrition, 2023)
Hyperuricemia (HUA) is a common metabolic disease, and its prevalence has been increasing worldwide. Pharmaceutical drugs have been used for controlling HUA but they all have certain side effects, which thus calls for discovering alternative options to prevent the development of HUA. Along this line, the current study aimed to evaluate the effects of Lactiplantibacillus pentosus P2000 (LPP) on the HUA induced by potassium oxonate and adenine in mice and also to explore the underlying mechanisms. The results demonstrated that oral administration with LPP significantly decreased serum uric acid and reduced renal inflammatory response by downregulating multiple inflammation pathways including apoptosis, NK-kB and TNF signaling pathway. We also found that LPP administration significantly promoted uric acid excretion by regulating expression of transporters in the kidney and ileum. In addition, LPP intake improved intestinal barrier function and modulated the composition of gut microbiota. Together, these results suggest that probiotics LPP may have a promising potential to protect against development of HUA and HUA-related renal damage, and its working mechanisms involve regulation of inflammation pathways and expression of transporters in the kidney and ileum.